PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN BAJU ANAK-ANAK DI PLATFORM SHOPEE - Tanjaya, Agustin (Universitas Widya Kartika Surabaya, 2024)
The purpose of this article is to summarize this problem, analyze consumer shopping behavior on the Internet in purchasing decisions and examine the context based on selected factors that influence consumer purchasing behavior on the Internet. E-commerce is electronic commerce related to the activities of buying, selling, marketing goods or services by utilizing internet communication networks as a form of future commerce. Consumers generally make purchasing decisions after evaluating the many choices of products or services offered to them.This part of the article focuses on the basis of consumer purchasing decisions which occur due to external and internal factors that consumers have within themselves. Internal factors such as physiological motivation to fulfill their needs. Apart from that, the learning, personality, attitudes and personal experiences through thoughts and feelings that consumers have gone through are psychological considerations for consumers. External factors include marketing information and the socio-cultural environment, for example religious views. This part of the research consists of descriptive qualitative research methods using in-depth interviews and observations.The questions focused on the subjective opinions of respondents from mothers who shop online and have children under five to 10 years old. Interview material includes: purchasing clothes on the Shopee platform, purchasing decisions, how often you buy clothes online, are you satisfied with shopping online at Shopee. Based on the results, the last part of this article outlines the proposal showing that 4 interviewees are very satisfied, 5 are less satisfied, 1 are not satisfied and the need to include online activities in daily life reaches a wider range of users.